2017
DOI: 10.4014/jmb.1710.10029
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Depletion by Silibinin Stimulates Apoptosis-Like Death in Escherichia coli

Abstract: Silibinin is the major active component of silymarin, extracted from the medicinal plant . Silibinin has potent antibacterial activity; however, the exact mechanism underlying its activity has not been elucidated. Here, we investigated the novel mechanism of silibinin against Escherichia coli. Time-kill kinetic assay showed that silibinin possess a bactericidal effect at minimal inhibitory concentration (MIC) and higher concentrations (2- and 4-fold MIC). At the membrane, depolarization and increased intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Silibinin could take effect on both. Firstly, silibinin is a scavenger of intracellular ROS 34. It’s significantly reduced drug-induced hepatocyte line LO2 cell death and even rescued the LO2 cell proliferative ability (Figure 5).…”
Section: Discussionmentioning
confidence: 98%
“…Silibinin could take effect on both. Firstly, silibinin is a scavenger of intracellular ROS 34. It’s significantly reduced drug-induced hepatocyte line LO2 cell death and even rescued the LO2 cell proliferative ability (Figure 5).…”
Section: Discussionmentioning
confidence: 98%
“…PS, a phospholipid component, is present in the inner lobules of the plasma membrane. When cells undergo apoptosis, PS is no longer limited to the cytoplasmic side, resulting in PS externalization [ 21 ]. Therefore, we evaluated whether beetroot extract can cause PS translocation of S. Typhimurium.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies reported that the depletion of ROS can affect signalling pathways and even lead to cell death [ 35 , 36 ]. In addition, one study has suggested that ROS consumption could induce ALD in E. coli [ 21 ]. To verify that the ALD of S. Typhimurium induced by beetroot extract is caused by ROS consumption, we treated S. Typhimurium with beetroot extract and hydrogen peroxide (H 2 O 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial cells were incubated for 2 h at 37 ℃ with H 2 O 2 , H 2 O 2 pretreated with 10 mM sodium pyruvate, H 2 O 2 pretreated with thiourea, or nor oxacin. Following incubation, DNA was extracted in an extraction solution (containing 100 mM NaCl, 10 mM Tris-Cl , 1 mM EDTA, 1 % SDS, 2 % Triton X-100, and 10 mg/mL proteinase K) as described in our previous study (Lee and Lee 2017). The 8-OHdG levels were estimated by competitive enzyme immunoassay method, using an Oxiselect Oxidative DNA Damage ELISA Kit (Cell Biolabs Inc., San Diego, CA, USA), according to the manufacturer's instructions.…”
Section: Assessment Of Oxidative Dna Damagementioning
confidence: 99%